2020
DOI: 10.18231/j.jchm.2020.028
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and determinants of workplace violence among family medicine residents at the joint program of Family Medicine in Jeddah, Saudi Arabia 2020

Abstract: Background: Workplace violence is a universal problem across all hospitals. Very few studies have reported violence incidents faced by residents during their residency. This study aimed to quantity family medicine resident's exposure of workplace violence and its consequences. Materials and Methods: A cross-sectional study was conducted among family medicine residents of joint program of Family medicine in Jeddah, Saudi Arabia in 2020. A structured questionnaire consists of demographic data, occupational histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…This finding showed that activities to report WPV cases were carried out, but the cases could still be underreported. This is comparable to a study by Alahmadi & Makhdoom [45], which demonstrated that less than 32% of HCWs reported violent events to their supervisors. Reporting is important in preventing future WPV cases, and healthcare employers should fully support it.…”
Section: Perception and Practice Towards Wpv Prevention Among Employe...supporting
confidence: 86%
“…This finding showed that activities to report WPV cases were carried out, but the cases could still be underreported. This is comparable to a study by Alahmadi & Makhdoom [45], which demonstrated that less than 32% of HCWs reported violent events to their supervisors. Reporting is important in preventing future WPV cases, and healthcare employers should fully support it.…”
Section: Perception and Practice Towards Wpv Prevention Among Employe...supporting
confidence: 86%